2022
DOI: 10.36233/0372-9311-246
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the epidemiological significance of molecular genetic factors in relation to the intensity of post-vaccination immunity against hepatitis B

Abstract: Introduction. Hepatitis B retains the status of socially significant infection and remains a major health problem worldwide, including the Russian Federation. The improvement of the effectiveness of the current complex of preventive measures, especially vaccination, is an important task for public health. Although vaccination against hepatitis B is highly successful, 5% to 10% of individuals do not experience a response to vaccine with an adequate level of antibodies to hepatitis B surface antigen (anti-HBs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Nevertheless, children who have received the hepatitis B vaccine experience a decline in the levels of anti-HBs due to several factors. It has been shown in different clinical studies that these factors include time after vaccination, gender, obesity, immunosuppression and variants of genotypes (18)(19)(20)(21)(22). In addition, it is suggested that the varying rates of anti-HBs positivity in clinical studies may be due to the age range of the patient group studied, socioeconomic differences in the study area and different vaccination protocols (23).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, children who have received the hepatitis B vaccine experience a decline in the levels of anti-HBs due to several factors. It has been shown in different clinical studies that these factors include time after vaccination, gender, obesity, immunosuppression and variants of genotypes (18)(19)(20)(21)(22). In addition, it is suggested that the varying rates of anti-HBs positivity in clinical studies may be due to the age range of the patient group studied, socioeconomic differences in the study area and different vaccination protocols (23).…”
Section: Discussionmentioning
confidence: 99%
“…Продолжительность напряженного иммуните та зависит от возраста людей в начале вакцина ции. Согласно ранее проведенным исследованиям, наиболее высокие показатели напряженности иммунитета констатированы у людей, вакциниро ванных в возрасте до 30 лет [22,26]. В нашей рабо те показано, что уровень antiHBs более 100 мМЕ/ мл и 400 мМЕ/мл в основном обнаруживается у людей более молодого возраста, и в дальнейшем с увеличением возраста уровень антител снижает ся.…”
Section: рисунок 2 распределение уровня напряженности поствакцинально...unclassified